1990
DOI: 10.1002/ddr.430200206
|View full text |Cite
|
Sign up to set email alerts
|

Drug discrimination and drug stimulus generalization with anxiolytics

Abstract: Work with lorazepam in two-lever food-maintained drug discrimination procedures with baboons and rats found greater specificity in the generalization profile when this drug was used as a training drug compared to studies with other benzodiazepines (BZ). That is, animals trained to discriminate lorazepam have not reliably made the drug response in tests with barbiturates, although animals trained to discriminate diazepam, chlordiazepoxide, triazolam, oxazepam, and sometimes midazolam commonly have done so. Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In studies with rats trained to discriminate midazolam, one reported generalization to pentobarbital (Garcha et al 1985) but a second from the same laboratory reported a maximum of 60% drug-appropriate responding in tests with pentobarbital (Rauch and Stolerman 1987). In recent work in our laboratory, pentobarbital occasioned drug lever responding in all rats trained to discriminate 0.32 or 1.0 mg/kg midazolam IP, with the pentobarbital generalization gradient shifted to the right for the group trained with the higher dose of midazolam (Ator 1989). The variables responsible for these differences in results across studies with midazolam remain to be determined.…”
Section: Discussionmentioning
confidence: 84%
“…In studies with rats trained to discriminate midazolam, one reported generalization to pentobarbital (Garcha et al 1985) but a second from the same laboratory reported a maximum of 60% drug-appropriate responding in tests with pentobarbital (Rauch and Stolerman 1987). In recent work in our laboratory, pentobarbital occasioned drug lever responding in all rats trained to discriminate 0.32 or 1.0 mg/kg midazolam IP, with the pentobarbital generalization gradient shifted to the right for the group trained with the higher dose of midazolam (Ator 1989). The variables responsible for these differences in results across studies with midazolam remain to be determined.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, the dose of LY379268 (3.0 mg/kg) that partially antagonized LSD-induced stimulus control also produced a significant decrease in the rate of responding. In studies of drug-induced stimulus control, the interpretation of intermediate results, whether intermediate generalization or antagonism, is problematical (Winter 1978;Ator 1990;Koek 1999). Nonetheless, the effects of LY379268 as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the introduction, both ethanol and allopregnanolone act as positive modulators of these receptor complexes in neurochemical and electrophysiological assays (Liedenheimer and Harris 1992;Hawkinson et al 1994). Furthermore, in drug discrimination procedures, there is a large degree of overlap between the discriminative stimulus effects of ethanol, the neuroactive steroids allopregnanolone and THDOC, and two other classes of GABA A receptor positive modulators, the benzodiazepines and barbiturates (Ator 1990;Ator et al 1993;Deutsch and Mastropaolo 1993). Although both ethanol and allopregnanolone can act to antagonize the cation conductance of the NMDA subtypes of glutamate receptors, allopregnanolone's effects are negligible at this receptor complex (Irwin et al 1994).…”
Section: Discussionmentioning
confidence: 99%